A REVIEW OF TECHNOLOGICAL DEVELOPMENTS IN SHRIMP AQUACULTURE PRODUCTION - Paul, Morfow Nkeze; Kasan, Nor Azman; Oben, Benedicta Oshuware Mbu; Osho, Friday Elijah (Indonesian Aquaculture Journal, 2025)
This review examines breakthrough technological developments in shrimp aquaculture, emphasizing key advances, remaining barriers, and policy implications for sustainable sector growth. Major technological innovations include biotechnology-driven improvements such as genetic selection, MAS and emerging CRISPR applications for disease-resistant stocks. AI-based monitoring and automation systems that optimize feeding and environmental control in real time; microbial approaches including probiotics and biofloc technology that enhance water quality and pond stability. Novel feeds incorporating insect, microbial and other alternative proteins to reduce dependence on fishmeal. These advances collectively improve productivity, animal health and environmental performance. However, adoption is hindered by high capital costs, technical complexity and limited farmer training. More so, uneven access to digital and genomic tools, particularly among small-scale producers. Addressing these barriers requires supportive policies that promote inclusive technology transfer, investment incentives, capacity building and regulatory frameworks for safe use of biotechnologies and data-driven systems. Overall, the review highlights how integrated biotechnological and AI-enabled innovations can transform shrimp aquaculture, provided that enabling policies ensure equitable, responsible and sustainable implementation.